ENDOTHELIN-1 CONTENT IN BLOOD AS A POSSIBLE BIOMARKER OF DIABETIC RETINOPATHY - Serdiuk, Anton (SWorld-Ger Conference proceedings, 2025)
In a cohort of patients (136 people) with type 2 diabetes mellitus and diabetic retinopathy, an increase in the content of endothelin-1 in the blood serum was found, which allowed to determine its borderline levels at different stages of DR and predict it